Monitoring and Diagnostic Load Testing of a Damaged Railway Bridge - Duvnjak, Ivan; Damjanović, Domagoj; Bartolac, Marko; Frančić Smrkić, Marina; Skender, Ana (Frontiers in Built Environment, 2019)
This study presents a complex experimental research of a damaged steel railway bridge. Before the reconstruction, the elastic behavior of the material was evaluated using the hole-drilling strain gauge method of determining residual stresses at the relevant cross-sections. During the reconstruction project (lifting of the structure), a short-term monitoring system was installed at the critical cross-sections for continuous recording of relative strain. The aim was to evaluate the quality of the reconstruction intervention and prevent further damages. Following a successful reconstruction, a diagnostic load testing was performed according to Croatian standards. The purpose of the load testing (static and dynamic) was to evaluate the ability of the bridge to carry the design loads and calibrate the finite element models. During static load testing loading vertical displacement was measured as well as relative strain. Dynamic load testing of the bridge was performed in order to determine the main dynamic parameters of the structure and to calculate the dynamic factor. In order to select the appropriate measurement parameters and methods used during this experimental research it was necessary to consider the bridge type, materials and reconstruction or strengthening interventions. Especially, since this bridge was an example of insufficient inspection and maintenance during service. A well-designed monitoring and diagnostic load testing needed to be performed in order to obtain useful results for the decision makers involved.